MATERNAL EMPLOYMENT AND CHILD OVERWEIGHT AND OBESITY:LITERATURE REVIEW - Romlah Romlah; Anjelina Puspita Sari (SEAJOM: The Southeast Asia Journal of Midwifery, 2020)
Working mothers are suspected of having links with the increase in excess weight (overweight and obesity) in children. Working mothers would be faced with a 'barter' situation of getting the least time spent with their children with the increasing family income. With little time the mothers spend with their children, they might lose control of the intake of food consumed by their children. When children eat more fast food containing high fat and sugar, the children will be more at risk for having excess weight. In fact, excess weight increases the children to suffer from diseases that were once only often suffered by adults. Diseases such as cardiovascular disease and type 2 diabetes mellitus are getting more common in children. Especially for girls, they will experience the process of pregnancy someday. Of course, obesity experienced by them will impact on the pregnancy when they remain obese as adults. Obesity in pregnancy may be at risk of the emergence of gestational diabetes that will allow bearing obese children as well. Therefore, before bad things happen in families with regard to the health of families, parents, especially mothers, should pay attention to the intake of foods consumed by children and devote more time to children in their growth period for Indonesia’s better generation.